2004
DOI: 10.1016/j.otohns.2004.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐Induced Malignancy of the Head and Neck

Abstract: C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 9 publications
2
37
0
7
Order By: Relevance
“…Since then, there have been several reports of patients developing radiation-induced sarcomas with shorter latency periods (as short as 2 years). 2,9,20 The shortest latency period in our group was 4.5 years. Laskin et al 21 reported a link between shorter latency periods and worse outcomes with radiation-induced soft-tissue sarcomas, but this relationship has not been further substantiated in the literature.…”
Section: Discussionmentioning
confidence: 46%
“…Since then, there have been several reports of patients developing radiation-induced sarcomas with shorter latency periods (as short as 2 years). 2,9,20 The shortest latency period in our group was 4.5 years. Laskin et al 21 reported a link between shorter latency periods and worse outcomes with radiation-induced soft-tissue sarcomas, but this relationship has not been further substantiated in the literature.…”
Section: Discussionmentioning
confidence: 46%
“…[18][19][20][21]29 In our study, we used the most common latency criteria of 3 to 4 years as reported by Arlen et al 21 The median latency in our series, 9.3 years, was consistent with data from other studies, in which the median latency ranges from 7.6 years to 22 years. [3][4][5][6][7][8][9][10][11]29 The shorter period of 7.6 years reported by Kuttesch et al 26 may be explained by the younger age of their patients. In addition, the administration of chemotherapy may shorten the interval between RT for the first cancer and the subsequent presentation of RIS.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
“…The 3-year OS rate for patients with RIS in our series (32.4%) was within the lower end of the wide range reported previously (8%-60% at 5 years). [3][4][5][6][7][8][9][10][11][12][13]34 The best survival outcome was reported by Tabone et al, 35 who reported that the OS and eventfree survival rates for 23 patients with radiation-related osteosarcoma at 8 years were 50% and 41%, respectively.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Almentioning
confidence: 99%
“…Radiation-induced malignancy (RIM) has been recognized since the early 1900s, and is believed to be caused by alterations in cellular DNA (DNA) and ribonucleic acid (RNA). 58,59 The disruption of nucleotide bonds alters protein synthesis and can result in a cancerous transformation if cellular reproduction is modified.…”
Section: Ionizing Radiation and Associated Risk Of Malignancymentioning
confidence: 99%